Binary blend based dye sensitized photo sensor using PCPDTBT and MEH-PPV composite as a light sensitizer - Qadir, K.W.; Ahmad, Z.; Sulaiman, K.; Yap, C.C.; Touati, F. (Elsevier, 2015)
In this research, we present a binary blend of two polymers, i.e., namely, poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta [2,1-b;3,4-b']dithiophene)-alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) and poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) as a sensitizer for a visible light dye sensitized photo sensor (DSPS). The combination of these two polymers covers almost whole visible light spectrum. The dependence of the current generation in the dye sensitized photo sensor has been investigated as a function of the varied incident light intensities. The output exhibits a linear relation as a function of incident light in the range of 0-30000 lux. The photoconductivity sensitivity of the DSPS lies within the range of 2.02x x 10(-5) x Sm/W. The average response and reset time of the sensor is found similar to 382 ms. Nevertheless, besides the consistency and repeatability, the economical and environmental friendly fabrication is an additional benefit of this sensor. (C) 2015 Elsevier B.V. All rights reserved.